Dialogue with Libâneo about didatics - Morais, Bruno Rogério Ferreira de; Camilo, Douglas Eleutério (Revista Hipótese, 2015)
Currently the teaching has been much studied , questioned and disseminated in education and it is very important to investigate and seek to solve problems in the low quality of teacher education . In this sense we intend to weave a dialogue with professor José Carlos Libâneo through articles that work the relationship of didactics with other disciplines, its importance in professional development, their valuation in pedagogy courses, its historical and cultural development.
Keywords: Didactics; Specific methodologies; Specific contents